Discovery of triazolopyridine GS-458967, a late sodium current inhibitor (Late INai) of the cardiac NaV 1.5 channel with improved efficacy and potency relative to ranolazine. Issue 13 (1st July 2016) - Koltun, Dmitry O.; Parkhill, Eric Q.; Elzein, Elfatih; Kobayashi, Tetsuya; Notte, Gregory T.; Kalla, Rao; Jiang, Robert H.; Li, Xiaofen; Perry, Thao D.; Avila, Belem; Wang, Wei-Qun; Smith-Maxwell, Catherine; et al.
Graphical abstract: Abstract: We started with a medium throughput screen of heterocyclic compounds without basic amine groups to avoid hERG and β-blocker activity and identified [1, 2, 4]triazolo[4, 3- a ]pyridine as an early lead. Optimization of substituents for Late INa current inhibition and lack of Peak INa inhibition led to the discovery of4h (GS-458967) with improved anti-arrhythmic activity relative to ranolazine. Unfortunately, 4h demonstrated use dependent block across the sodium isoforms including the central and peripheral nervous system isoforms that is consistent with its low therapeutic index (approximately 5-fold in rat, 3-fold in dog). Compound4h represents our initial foray into a 2nd generation Late INa inhibitor program and is an important proof-of-concept compound. We will provide additional reports on addressing the CNS challenge in a follow-up communication.